Mini percutaneous nephrolithotomy: its role in the management of renal stone and our tertiary care centre experience - Thakur, Avinash Pratap Singh; S., Darsan (International Journal of Research in Medical Sciences, 2020)
Background: Miniaturized percutaneous nephrolithotomy (PCNL) procedures for urolithiasis have gained increased popularity in recent years. To decrease the complications of conventional PCNL by reduced tract size led to the development of Mini PCNL, which makes the use of 15-18F sheaths in place of 24-30F of conventional PCNL. It has developed rapidly and become a popular technique of renal stone management with reduced morbidity and excellent outcome. Authors report our experience with Mini PCNL for the treatment of renal stone. Methods: In between his August 2015 and January 2018, sixty patients with the diagnosis of unilateral single medium size (8-20mm) renal stone were identified. Patient’s demographical, clinical, diagnostic and procedural data were recorded. All patients were evaluated by history taking, physical examination and laboratory investigations. Radiological evaluation was done with X ray kidney, ureter and bladder region (KUB) and also with renal ultrasonography followed by computed tomography (CT). All patients underwent Mini PCNL using 12F nephroscope and 16.5/17.5F sheath. Holmium: YAG laser was used for stone fragmentation. No nephrostomy tube was used routinely. Treatment outcome was assessed in terms of operative time, haemoglobin drop, hospital stay and stone free rate. Results: Complete stone fragmentation was achieved in 41 out of 60 patients using Mini PCNL, so initial stone free rate was 68.3%. After 4 weeks of surgery total 53 patients were stone free (88.3%), 5 patients required some auxiliary procedure for complete clearance of stone and other 2 were managed conservatively. The mean operative time was 48.28 min, mean haemoglobin drop was 0.74gm/l and mean postoperative hospital stay was 54.22 hours. After 12 weeks postoperatively all patients were stone free. There were no significant postoperative complications, and all had good quality of life. Conclusion: Mini PCNL technique appears to be safe and effective alternative to conventional PCNL for moderate size renal calculi. It is usually related to less blood loss and shorter hospital stay than the standard method. It can achieve good stone-free rates with minimal complications and low morbidity. Mini PCNL can also be considered as a good alternative to retrograde intrarenal surgery and shockwave lithotripsy in selected cases. However, further high quality studies with larger sample size are required in future.